DEVELOPING SPEAKING MATERIALS BY INCORPORATING CHARACTER BUILDING ASPECTS FOR EIGHTH GRADERS AT SMPN 3 BATU - Pratiwi, Indra; Latief, Mohammad Adnan (LET: Linguistics, Literature and English Teaching Journal, 2015)
Based on the needs analysis stage, it is found that the existing speaking materials do not employ character building aspects as demanded by the curriculum.Therefore, new speaking materials that incorporate character building aspects need to be developed. Research and Development (R&D) by Borg and Gall (1983)was used in this research involving the needs analysis, material development, expert validation, try-out, and final product.Five units with various tasks and activities which include both individual and group activities were developed containing the topics ofFriendship, Speak Up, Making Telephone Call,Share Your Story, and Indonesian Folktales. The researchers adopted the task-based and project-based learning principles. Particular aspects of character building were chosen based on the activities to be done by the students so that the students will be aware that they learnmoral values during the lesson. To help the English teachersthis materials provides teacherâs guide so that the teacher knows what s/he should do to teach character building aspects. After being validated by two education experts and tried out, the product is considered appropriate and acceptable to be taught to eight graders at SMPN 3 Batu.